International Conference on Quality, Innovation and Sustainability – ICQIS2020 - Book of Abstracts - Pereira, Mário Rito (2021)
This book gathers the abstracts submitted and presented at the 2nd International Conference on Quality, Innovation and Sustainability, organized by the Polytechnic of Leiria and the Polytechnic Institute of Viana do Castelo on November 19 and 20, 2020. Abstracts are organized by session, and include keynote presentations, ordinary presentations and the poster session.